influence of a proposed model based on the "Paivio" theory on fifth-grade literary students' history collection and rational thinking (Journal of the College of Basic Education, 2022)
This research aims to identify (the effect of a proposed model according to Paivio's theory in the collection of history and rational thinking among fifth-grade literary students), and the research objective can be detailed to the following:1-Building a teaching model according to the "Paivio" theory.2- To verify the effectiveness of the proposed model in the collection of history and rational thinking for fifth literary grade students. To achieve the goal of the research, a teaching model was built according to the "Paivio" theory, using the descriptive research method, and to verify its effect, the following two null hypotheses are formulated: 1: There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who study according to the proposed model and the average scores of the control group students who study in the usual way in the post-achievement test. 2-There is no statistically significant difference at the significance level (0.05) between the average scores of the experimental group students who study according to the proposed model and the average scores of the control group students who study in the usual way in the rational thinking scale, and the research is determined by a sample of fifth-grade literary students from Ibn Al-Nafees Preparatory School in Al-Qadisiyah Governorate for the academic year (2020-2021) . The researcher chose the experimental design with partial control, and two divisions of the fifth literary class were chosen randomly, and the research sample amounted to (59) students, with (30) students in the experimental group, and the division (C) who studied with the proposed model, and the control group (29) students represented by a division (A). Those who studied in the usual way and were equal between them in the variables (chronological age, previous information, intelligence, rational thinking scale, parents’ academic achievement), and the researcher prepared a test for the final achievement, and made sure of its honesty, stability, difficulty factor, discriminatory strength of its paragraphs, and the effectiveness of the wrong alternatives, as well as the researcher prepared a scale for rational thinking and made sure of its validity, stability, difficulty factor and discriminatory power. At the end of the experiment, the researcher applied his research tools and treated his data statistically using (spss20). The results showed the superiority of the students of the experimental group who studied with the proposed model over the control group who studied in the usual way in achievement. In light of the results of the research, the researcher recommended the need to use the proposed model in achievement and rational thinking. The researcher also presented a set of recommendations. For proposals, most notably the conduct of studies similar to the current study on other study stages for both genders. As well as identifying the effectiveness of the proposed model on other dependent variables such as creative thinking, self-confidence, attitude towards material, and others.